Three-dimensional nanowire networks fabricated by ion track nanotechnology and their applications - M. F. P. Wagner; K.-O. Voss; C. Trautmann; M. E. Toimil-Molares (EPJ Techniques and Instrumentation, 2023)
Abstract The existing and future accelerator facilities at GSI and FAIR offer unique opportunities for interdisciplinary research, especially for material science and nanotechnology. On their way through polymers, swift heavy ions with GeV energy deposit enormous energy densities along their trajectory, generating long nanoscopic damage trails known as ion tracks. Ion-track technology utilizes the small track size (few nm) combined with the extensive track length (up to 100 μm and more) to synthesize and control the geometry of high-aspect-ratio nanostructures such as tailored nanochannels and nanowires. In particular, electrodeposition and ion-track nanotechnology provide an excellent platform for developing unique 3D networks of nanowires with controlled dimensions, composition and crystallographic properties. Here, a summary of recent results obtained on the synthesis and characterization of stable 3D architectures of semiconductor and semimetal nanowires, and their implementation in the fields of photoelectrochemistry and thermoelectrics, is presented.